The role of work engagement and organizational commitment in improving job performance - Faqih Nabhan; Munajat Munajat (Cogent Business & Management, 2023)
This study aimed to identify the factors that can improve job performance by scrutinizing various variables, namely organizational identification, Islamic work ethic, work engagement, and organizational commitment, based on the perspective of engagement theory. The respondents consisted of 206 faculty members from Islamic state universities in Central Java, Indonesia, with a participation rate of 72%. The data was analyzed using structural equation modeling and hypotheses were tested using the AMOS 24 application. The result showed that work engagement and organizational commitment strengthened the effect of organizational identification and Islamic work ethic on job performance. Furthermore, these findings provided novel insights from the perspective of engagement theory, where work engagement and organizational commitment play pivotal roles in enhancing job performance. The study demonstrated that organization identification did not have a direct effect on job performance, while Islamic work ethic promoted the development of organizational commitment.
Keywords: 650; Islamic work ethic; job performance; organizational commitment; organizational identification; work engagement